Causal relationship in gut microbiota and upper urinary urolithiasis using Mendelian randomization - Zhang, Ruiqiao; Zhao, Weijie; Zhao, Ruijie; Zhao, Yunhai; Zhang, Yanlong; Liang, Xuezhi (Frontiers in Microbiology, 2023)
Background：Several reports in recent years have found an association between gut microbiota and urinary stones. However, the causal relationship between them remains to be clarified. Methods: Genetic variation is used as a tool in Mendelian randomization for inference whether exposure factors have a causal effect on disease outcomes. We selected summary statistics from a large genome wide association study of the gut microbioma published by the MiBioGen consortium as an exposure factor and urolithiasis data from FinnGen GWAS as a disease outcome. Then a two-sample Mendelian randomization analysis was performed by applying Inverse variance weighted, MR-Egger ,maximum likelihood,and weighted median. In addition, sensitivity analysis was done to avoid bias of the results. Results: IVW results confirmed that Barnesiella（OR = 0.695，95%CI：0.551–0.877，P = 2.20 × 10−3）, Clostridium sensu_stricto_1（OR = 0.777，95%CI：0.612–0.986，P = 0.0380）, Flavonifractor（OR = 0.711，95%CI：0.536–0.944，P = 0.0181）, Hungatella（OR = 0.829，95%CI：0.690–0.995，P = 0.0444） and Oscillospira（OR = 0.758，95%CI：0.577–0.996，P = 0.0464）had a protective effect on renal stones while Eubacterium xylanophilum（OR =1.26，95%CI：1.010–1.566，P = 0.0423） had the opposite effect in total 119 genera. Sensitivity analysis did not find outlier SNPs. Conclusion：In conclusion, a causal relationship was found between several genera and urinary stones. However, we still need further randomized controlled trials to validate.